Comparative Study of Sun Drying and Solar Tent Drying of Hyperopisus bebe occidentalis - Ojutiku, R.O.; Kolo, R.J.; Mohammed, M.L. (Pakistan Journal of Nutrition, 2009)
An experiment was conducted to investigate the effect of two drying processing methods on the nutritional qualities of Hyperopisus bebe. The two methods used were solar tent dryer and traditional sun drying methods. The experimental fish were dried for 120 h (5 days). The results of proximate analysis showed significant difference (p<0.05) between the two techniques. Organoleptic evaluation showed no physical damage, no discolouration in the treatments and both had firm texture though fishes under traditional sun drying were infected by insects.